Ecoeficiência na indústria de petróleo: o estudo do craqueamento catalítico na Petrobrás - Ramirez Corradi, Samuel (2008)
The concern with the environment is not a recent phenomenon, however, during some time the quarrel over ambient elements did not succeed to reach similar importance as subjects like productivity and quality. The diagnosis of ambient problems with serious consequences in the whole world contributed to renew the concern with the environment and the ambient element acquired high importance in daily activities and in the activities of manufacture and commerce. During many years the ambient politics and regulations were seen as limits to the production or expansion of the productive activities. In the present work we developed a study which demonstrates, in fact this picture is not real. Therefore it is possible to act in efficient considering ambient and economics. A concept that searchs to add efficiency in operations, productiveness and economics to the respect with the environment is the ecoefficiency. In the present work a study of case in the area of ecoefficiency was developed and presents some innovations developed and adopted in the oil industry that had contributed for the company to reach greater efficiency using natural resources, with lesser losses and greater production of demanded derivatives of oil and thus contributing for higher productive, economic and ambient efficiency.